Early signs of damage to the brain as a target organ in hypertension - T. M. Ostroumova; O. D. Ostroumova; V. A. Parfenov (Неврология, нейропсихиатрия, психосоматика)
The paper reviews the data available in the literature on and the results of the authors' own investigations of the signs of brain damage in hypertension in its early stages. The signs of early brain damage in hypertension can be considered as deteriorated control functions, white matter hyperintensities (WMH), as evidenced by the standard modes of magnetic resonance imaging (MRI), decreased fractional anisotropy in the frontal lobes, as shown by diffusion tensor MRI, and reduced cerebral perfusion. The latter two signs are detected even in hypertensive patients without WMH. Cognitive function testing and brain MRI using special regimens make it possible to identify a group of hypertensive patients at higher risk for cerebrovascular complications just in the early stages of the disease.